State-of-the-art combination treatment strategies for advanced stage non–small cell lung cancer - Yao, Yongfang; Fareed, Rameesha; Zafar, Aliya; Saleem, Kalsoom; Huang, Tao; Duan, Yongtao; Rehman, Masood Ur (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC) is most abundant type of epithelial lung cancer being diagnosed after 40% of invasions of excrescence in pulmonary tissues. According to WHO, 30% of NSCLC patients can be cured if early diagnosed and treated. Mutations play an important role in advanced stage NSCLC treatment which include critical proteins necessary for cellular growth and replication. Restricting such mutations may improve survival in lung cancer patients. Newer technologies include endoscopic bronchial ultrasonography and esophageal ultrasonography. Currently, policymaking or decision-making for treatment regimens merely depends on the genomic alterations and mutations. DNA sequencing, methylation, protein, and fragmented DNA analysis do NSCLC screening. Achievement of these goals requires consideration of available therapeutics in current anticancer approaches for improving quality of life and treatment outcomes for NSCLC patient. The specific goals of this review are to discuss first-line and second-line therapies for advanced-stage NSCLC and molecularly targeted therapy including thoughtful discussion on precise role of treatment strategies in specific tumors. Also, concerned diagnostics, new clinical trial designs, and pursuing appropriate combinations of radiotherapy and/or chemotherapy with biological therapy for exceptional cases considering resistance mechanisms and palliative care, will be discussed.